1994
DOI: 10.1021/j100069a025
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of the Solution-State Dynamics and Solid-State Structure of Tri-n-butyltin Fluoride

Abstract: Dynamics and structure of tri-n-butyltin fluoride in n-hexane solutions were probed using (tin-1 19) nuclear magnetic resonance spin relaxation methodologies. Significant relaxation-induced polarization transfer effects were observed and exploited. The experimental observations indicate that the tri-n-butyl fluoride exists in a polymeric form in solution. For a 0.10% (w/w) solution at 25 OC, NMR reveals significant orientational/ exchange relaxation on both the microsecond and nanosecond time scales. Solution-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Tributyltin hydride then enters the B(C 6 F 5 ) 3 catalytic cycle to produce the corresponding vinylstannanes. 19 The NMR data for the Sn−F species indicated that it is not Bu 3 SnF, which appears as a triplet at δ −10 ppm with J = 1350 Hz in hexane, 26 or a Bu 3 SnF• B(C 6 F 5 ) 3 adduct, which appears at −18 ppm in toluene. 20 To further eliminate the possibility of Bu 3 SnF involvement, hydrostannation of phenylacetylene (3) was performed with premade tributyltin fluoride (1 equiv), B(C 6 F 5 ) 3 (20 mol %), and PMHS (2 equiv).…”
mentioning
confidence: 99%
“…Tributyltin hydride then enters the B(C 6 F 5 ) 3 catalytic cycle to produce the corresponding vinylstannanes. 19 The NMR data for the Sn−F species indicated that it is not Bu 3 SnF, which appears as a triplet at δ −10 ppm with J = 1350 Hz in hexane, 26 or a Bu 3 SnF• B(C 6 F 5 ) 3 adduct, which appears at −18 ppm in toluene. 20 To further eliminate the possibility of Bu 3 SnF involvement, hydrostannation of phenylacetylene (3) was performed with premade tributyltin fluoride (1 equiv), B(C 6 F 5 ) 3 (20 mol %), and PMHS (2 equiv).…”
mentioning
confidence: 99%